Forced Money (Dwangsom) in the Indonesian State Administrative Court System and Astreinte in French Conseil d'État - Erlangga, Sandya; Disyon, Huta; Anh, Hoàng Thảo (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2023)
The administrative court system in Indonesia shares fundamental similarities with the state administrative court system in France. This study aims to conduct a comparative analysis of the judicial systems in Indonesia and France, specifically focusing on examining the regulation of forced money penalties (dwangsom) in Indonesia. It has been around for about fourteen years since Law Number 51 of 2009 concerning the Second Amendment to Law Number 5 of 1986 concerning the State Administrative Court ("State Administrative Court Law); there are no implementing regulations, thus hindering the imposition of forced money in the decisions of the State Administrative Courts in Indonesia. As per the author's assertion, this circumstance can potentially diminish the effectiveness of the State Administrative Courts in Indonesia, undermining their ability to enforce judgments. In the context of legal matters, it is noteworthy to mention that the French Conseil d'État has taken measures to govern the issue of forced money penalties (astreinte), specifically regarding their execution and associated costs. The study used normative juridical. It also used a comparative method to normative juridical methods to analyze Indonesia's principles, norms, and legal system. Study findings indicate the urgent need to establish regulations on imposing forced money penalties within the Indonesian Administrative Court. This is crucial to mitigate challenges associated with enforcing forced money decisions, minimize financial losses resulting from errors in official services, and address the legal uncertainty surrounding the determination of forced money costs.